The new complete book of food a nutritional, medical, and culinary guide - Rinzler, Carol Ann; Gale Group (New York Facts On File, 2009)
Provides the nutritional, medical, culinary, and consumer information essential to planning a good diet and proper food handling.
Electronic reproduction.
Keywords: Food; Nutrition; Electronic books